Dual energy CT in the management of antiplatelet therapy in patients with acute ischemic stroke for carotid obstruction. Issue 2 (April 2020) - Murias, Eduardo; Vega, Pedro; Lopez-Cancio, Elena; Peña, Jorge; Morales, Edison; Benavente, Lorena; González, Montserrat; Larrosa, Davinia; Rico, Maria; Riesco, Nuria; Cadenas, Maria; Jimenez, Jose Maria; et al.
Background and purpose: Acute tandem occlusions often require carotid stenting. Combination of mechanical and pharmacologic therapies in addition to antiplatelet drugs administered to prevent acute stent thrombosis might increase the risk of intracerebral hemorrhage. We present a protocol of antiplatelet regimen based on early post-procedural dual-energy CT (DE-CT). Material and methods: Fifty consecutive stroke patients with tandem occlusions treated with acute carotid stenting after intracranial thrombectomy and TICI 2b/3 were reviewed. All patients received intravenous lysine acetylsalicylate during the procedure. Dual (aspirin+clopidogrel with or without clopidogrel load, groups A and B, respectively) or mono (aspirin) antiplatelet regimen (group C) was administered 12–24 h later according to brain DE-CT findings. Carotid ultrasonography was performed at 24 h and before discharge. We evaluated the rate of subsequent symptomatic intracranial hemorrhage (SICH) and acute stent thrombosis in each group. Results: Between June 2014 and December 2016, 50 patients were included (mean age 66 years, 76% men, baseline NIHSS 16, median time from symptom onset to recanalization 266 min). According to DE-CT, 24 patients were assigned to group A, 19 to group B and 7 to group C (4 of them had SICH at that time). One patient suffered a subsequent SICH (belonging to group B). There was only one stent thrombosis without clinical repercussions in group B. Conclusions: DE-CT may contribute to select antiplatelet regimen after acute carotid stenting in tandem occlusions.